Beyond surveillance: leveraging the potential of next generation sequencing in clinical virology - Aulicino, Paula C.; Kimata, Jason T. (Frontiers in Tropical Diseases, 2024)
The COVID-19 pandemic demonstrated the strength of massive sequencing or next generation sequencing (NGS) techniques in viral genomic characterization. Millions of complete SARS-CoV-2 genomes were sequenced in almost real time. Laboratories around the world dedicated to the molecular diagnosis of infectious diseases were equipped with cutting-edge technologies for deep sequencing, coupled with strengthening or development of previously limited bioinformatics capacities. Almost 5 years have passed from the initiation of the COVID pandemic, and, opposed to what could be envisioned as an opportunity for viral genomics to expand, this has essentially scaled back in most clinical settings. Most of NGS equipment and capacities in many regions of the world have been repurposed for the study of cancer driver mutations, microbiome-related diseases, and pharmacogenomics, as the most important applications in health. Although financial constraints can limit their implementation, technical, regulatory, medical and data management factors are also part of the equation that will or will not make NGS a real game changer for advancing healthcare and guiding clinical decisions related to viral infections.